Development and Demonstrational Instantiation of a Method for the Structured Content Analysis of Smartphone Apps - Tobias Weiss; Susanne Strahringer (Complex Systems Informatics and Modeling Quarterly)
The publication discusses the adaptation of dedicated known methods for structured content analysis for the usage of smartphone apps, taking into account the specifics of these dynamic media types and resulting consequences for the procedure and content rating. The background is the increasing popularity of apps and the growing demand for precise analysis of the status quo regarding the content and functions of apps on the market, especially within design-oriented business informatics. Within the literature, no uniform, comparable and systematic approach to this could be identified so far. Therefore, an existing standard for the evaluation of apps from the medical context has been adapted for general application to apps. This provides a helpful procedure for researchers, practitioners, and students and ensures consistency across studies. The feasibility of the proposed method and assessment standard were confirmed by a successful demonstrational instantiation based on an app review of energy information systems for private customers.